Influência do sistema terrestre no comportamento das variáveis limnológicas e na reflectância espectral de sistemas aquáticos - Ferreira, Aline Batista (2008)
This study aimed evaluating the impacts of landuse in the limnological variables and spectral reflectance of the water of three watersheds, located in the central region of Rio Grande do Sul. The areas studied were: the watershed of the Cadena Creek and Vacacaí Mirim and Ibicuí-Mirim rivers - RS (Brazil). To obtain the data of the coverage and landuse topographic charts and images CCD/CBERS 2 were used (October 2006). Images were processed using the software IDRISI 32, and the supervised classification allowed the identification and quantification of different landuse areas (Urban Area, Agriculture, pastures, fields and small size vegetation, water and Forestation). Limnological variables examined were: water transparency, total suspended solids (TSS), total dissolved solids (TDS), water and air temperature, pH and electrical conductivity (EC). It performed ten field trips that occurred on days 21, 23, 26, 28 and 30/11 and 03, 05, 07, 10 and 12/12, 2007. Measures were taken with the radiometric spectroradiometer FieldSpec3 (spectral range of 350 to 2500nm and spectral resolution ranging from 3 to 10nm), the collections were performed on days 11/30/2007 and 12/07/2007. Identification of the landuse allowed the evaluation of the variables behavior for each limnological watershed. Concentrations of TDS and TSS were lower in the river Ibicuí- Mirim SB, due to the increased presence of vegetation on its banks, which also influenced their reflectance (low albedo). In Cadena Creek the highest values of TDS were found and the river Vacacaí-Mirim the TSS was the highest. The EC assumed high values in the river Vacacaí-Mirim (207 to 397 μScm-1), and in Cadena Creek (459 to 563 μScm-1), due to the proximity to urban areas, mainly the creek for about 63% of their urban area. The pH variations occurred among the three watersheds, between 6.0 and 7.0. Due to the high concentration of organic matter on the Vacacaí-Mirim is river surface, it presented a range of green wavelength (between 500nm and 600nm) most expressive reflectance values than the watershed of Cadena Creek and Ibicuí-Mirim River. The integrated analysis of the results showed how the metabolism and its aquatic reflectance are influenced by the way of the landuse in each type of watershed, being the rural area the most affected on the TSS and the urban reflectance on the TDS.